Screening and Identification of Key Genes for Activation of Islet Stellate Cell - Wang, Xiaohang; Carvalho, Vladmir; Wang, Qianqian; Wang, Jinbang; Li, Tingting; Chen, Yang; Ni, Chengming; Liu, Lili; Yuan, Yang; Qiu, Shanhu; Sun, Zilin (Frontiers in Endocrinology, 2021)
Background: It has been demonstrated that activated islet stellate cells (ISCs) play a critical role in islet fibrogenesis and significantly contribute to the progression of type 2 diabetes mellitus. However, the key molecules responsible for ISCs activation have not yet been determined. This study aimed to identify the potential key genes involved in diabetes-induced activation of ISCs. Method: Stellate cells were isolated from three 10-week-old healthy male Wistar rats and three Goto-Kakizaki (GK) rats. Cells from each rat were primary cultured under the same condition. A Genome-wide transcriptional sequence of stellate cells was generated using the Hiseq3000 platform. The identified differentially expressed genes were validated using quantitative real-time PCR and western blotting in GK rats, high fat diet (HFD) rats, and their controls. Results: A total of 204 differentially expressed genes (DEGs) between GK. ISCs and Wistar ISCs (W.ISCs) were identified, accounting for 0.58% of all the 35,362 genes detected. After the Gene Ontology (GO) and Kyoto encyclopedia of genes and genomes (KEGG) enrichment analyses, the mRNA levels of these genes were further confirmed by real-time PCR in cultured ISCs. We then selected Fos, Pdpn, Bad as the potential key genes for diabetes-induced activation of ISCs. Finally, we confirmed the protein expression levels of FOS, podoplanin, and Bad by western blotting and immunofluorescence in GK rats, HFD rats, and their controls. The results showed that the expression level of FOS was significantly decreased, while podoplanin and Bad were significantly increased in GK.ISCs and HFD rats compared with controls, which were consistent with the expression of α-smooth muscle actin. Conclusions: A total of 204 DEGs were found between the GK.ISCs and W.ISCs. After validating the expression of potential key genes from GK rats and HFD rats, Fos, Pdpn, and Bad might be potential key genes involved in diabetes-induced activation of ISCs.